Global Corporate Finance / Text and Cases - Kim Seung H; Kim Suk H (Blackwell Publishing, 1999)
This book introduces students to principles essential to understanding global financial problems and multinational problem-solving policies and techniques. Preface, Acknowledgements, The Global Financial Environment, Introduction, Motives for World Trade and Foreign Investment, The Balance of Payments, The International Monetary System, Foreign Exchange Risk Management, An Overview of the Foreign Exchange Market, Currency Futures and Options, Financial Swaps, Exchange-Rate Forecasting, Foreign Exchange Risk Management, Financing International Transactions, International Financial Markets, International Banking Operations and Country, Financing Foreign Trade, Financing Foreign Investment, Global Asset Management, Current Asset Management, International Portfolio Investment, Foreign Direct Investment Strategy, Multinational Capital Expenditure Analysis, The Cost of Capital for Foreign Projects, Political Risk Management, Global Reporting and Controlling, Multinational Accounting, International Taxation, International Transfer Pricing, Comprehensive Cases in Global Finance, Glossary.